Dispositivo de resistência com vibrações mecânicas para treinamento muscular - Souza, Márcio Peres de (2012)
Currently, the practice of resistance exercises in order to obtain improvements in athletic performance, aesthetic or physical therapy goals are becoming an important and common practice in society. In general, the practice of these exercises use conventional equipment with cables and weight stacks. Recently, other training types were incorporated into the conventional equipment’s using mechanical vibration systems. It is know that mechanical vibrations have direct action on biological systems and have been used to prevent degenerative diseases. But is not known clearly yet the biomechanical phenomena related to the use of mechanical vibrations, mainly, when the vibration is applied into direction muscles contraction. The objective of this work was to design a support structure with mechanical vibration applied to human arm to brachial biceps muscle training. The design conception and discussion of this structure is presented. However their final dimensions and validation will be done in future works. The principal contribution of this dissertation is the development of computational models and experimental modeling to identify a dynamic model to human arm, estimating the stiffness parameters values, inertia and damping. These parameters will be used to validate the structure sustention model with vibrations. The proposed device will be manufactured in cylindrical shape carbon fiber with possibility to vary the frequency and amplitude by unbalanced mass system. The use of this device with cam system will enable to train at higher speeds with additional mechanical vibration application controlled in to direct brachial biceps muscle shortening of the individual who performs the dynamic training strength. It is believed that after construction and validation, this device will help to understand the real influences of mechanical vibration in skeletal muscle system.